Catalyst Lifetime Analysis for High-Temperature Shift Converter (104-D1) at Urea Factory - Rahmatullah, Rahmatullah; Putri, Rizka Wulandari; Mahendra, Bobi; Arofi, Hegar Tifal; Hadi, Cecep Sumiratna (Universitas PGRI Madiun, 2023)
High Temperature Shift (HTS) Converter (104-D1) have a function to convert CO gas into CO2 in the ammonia unit. The presence of CO could be poisoning the catalyst in the ammonia converter. The performance of HTS (104-D1) was ideal if the percentage of CO outlet is above 3.41 mol % dry basis. The performance of HTS (104-D) was influenced by operating conditions (pressure and temperature) and the ratio of steam to carbon. The increase in temperature in HTS (104-D1) can increase in the reaction rate and a decrease in CO conversion due to a decrease in catalyst performance. The research aims to find out how the performance of HTS (104-D1) after Turn Around process (catalyst replacement) that reviewed based on the operating conditions and the resulting CO conversion. The analysis was carried out by comparing the CO conversion from the actual data with the CO conversion from the design data by using the regression equation method to predict the lifetime of the catalyst. CO conversion obtained from the design data is 69.42 %. Conversion of actual data in June, July, August, September and October was 67.43 %; 78.32 %; 77.93 %; 77.75 %; and 77.40 %. The lifetime of the HTS catalyst (104-D1) PUSRI-IIB was estimated to be used up to 5 years after Turn Around process.